Magnetic Depth Estimation for Dyke-Like Bodies by Using Fraser Filter – A New Scheme - Fitian R. Al-Rawi (مجلة جامعة الانبار للعلوم الصرفة, 2009)
Abstract: Depth estimation for dyke like bodies has been investigated through using Fraser filter. The procedure consists of applying Fraser filter to magnetic profiles data due to dyke-like sources. Three ways of calculation are followed to estimate the depths of these bodies and good results with low percentage errors are achieved. Firstly, defining the width of the profile at two third of maximum amplitude of the residual filtered out data gives directly the depth to the top of the body. Secondly, plotting filtered data values at various levels of amplitudes against distances between points of these levels at the two lines of maximum slopes of the residual profile give a straight slope line. A projection line from the amplitude axis at two third value of maximum amplitude to the slope line read directly at distance axis the depth to the top of the body. Thirdly, the zero crossover distance defined on the plot of filtered data against distance divided by two gives directly the depth to the top of the body.Low percentage errors are found by applying the three ways, although there are small variations between them, most values are too low. This method of depth estimation is also applied to published field example and the result is too good. The procedure is simply applied and it gives a reliable and accepted depth values compared with actual depth values of the dyke-like bodies. The present procedure can be considered as a new scheme for depth estimation of magnetic sources if one considers the low percentage errors and the success of the results particularly in mid latitudes.